2010
DOI: 10.1021/bc900406m
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II)−Dendrimer Conjugates: Synthesis and Investigations on Cytotoxicity, Cellular Distribution, Platinum Release, DNA, and Protein Binding

Abstract: A set of polyamidoamine dendrimers were modified in such a way that they are able to act as carrier and drug delivery systems for cytostatics. The terminal binding of the non-proteinogenic D,L-2,3-diaminopropionic acid allowed the attachment of the cytotoxic PtX(2) moiety (X = Cl, I: A(PtI(2))(2), A(PtCl(2))(2), B(PtI(2))(2), B(PtCl(2))(2)), while the 2-carboxypentanedioic acid acted as leaving group for [meso-1,2-bis(4-fluorophenyl)ethylenediamine]platinum(II) ((m-4F-Pt)(3)C, (m-4F-Pt)(3)D). Poly(ethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 38 publications
(45 reference statements)
0
32
0
Order By: Relevance
“…Significant activity was only observed in vivo in L1210 murine leukaemia and B16 melanoma bearing mice. In another study, in vitro cytotoxicity was only observed when a platinum-dendrimer complex was incubated with cells for very long periods of time: 75 to 225 h [33]. Therefore our in vitro results do not necessarily imply that the drug-dendrimer complexes developed in this study are not active and different methods for determining cytotoxicity, including in vivo experiments, may be necessary for dendrimer-based delivery systems to be investigated properly.…”
Section: In Vivo Effectivenessmentioning
confidence: 68%
“…Significant activity was only observed in vivo in L1210 murine leukaemia and B16 melanoma bearing mice. In another study, in vitro cytotoxicity was only observed when a platinum-dendrimer complex was incubated with cells for very long periods of time: 75 to 225 h [33]. Therefore our in vitro results do not necessarily imply that the drug-dendrimer complexes developed in this study are not active and different methods for determining cytotoxicity, including in vivo experiments, may be necessary for dendrimer-based delivery systems to be investigated properly.…”
Section: In Vivo Effectivenessmentioning
confidence: 68%
“…Full generation PAMAM dendrimers have amine surface groups that can be used to irreversibly bind platinum, thus using the dendrimer as part of the structure of the drug rather than as a delivery vehicle (Kapp et al 2010). Half-generation PAMAM dendrimers have carboxylate surface groups and can bind cationic platin drugs via electrostatic interactions (Pisani et al 2009).…”
Section: Dendrimersmentioning
confidence: 99%
“…Instead of using the cellular Pt accumulation (ng of Pt per 10 6 cells), the accumulation ratio (AR), a concept similar to the "accumulation grade of factor" previously defined by Gust et al [53], was employed in the present paper. AR is the dimensionless ratio between the cellular Pt concentration (taking into account the experimentally measured cell volume) and the extracellular Pt concentration (i.e.…”
Section: Lipophilicity and Cellular Accumulation Of 1-4 Complexes On mentioning
confidence: 99%